The Permian–Triassic boundary Lung Cam expanded section, Vietnam, as a high-resolution proxy for the GSSP at Meishan, China. (14th June 2019) - Ellwood, Brooks B.; Nestell, Galina P.; Lan, Luu Thi Phuong; Nestell, Merlynd K.; Tomkin, Jonathan H.; Ratcliffe, Kenneth T.; Wang, Wei-Hsung; Rowe, Harry; Nguyen, Thanh Dung; Nguyen, Chien Thang; Dang, Tran Huyen
Abstract: The Lung Cam expanded stratigraphic succession in Vietnam is correlated herein to the Meishan D section in China, the GSSP for the Permian–Triassic boundary. The first appearance datum of the conodont Hindeodus parvus at Meishan defines the Permian–Triassic boundary, and using published graphic correlation, the Permian–Triassic boundary level has been projected into the Lung Cam section. Using time-series analysis of magnetic susceptibility (χ) data, it is determined that H. parvus arrived at Lung Cam ∼18 kyr before the Permian–Triassic boundary. Data indicate that the Lung Cam section is expanded by ∼90 % relative to the GSSP section at Meishan. Given the expanded Lung Cam section, it is possible to resolve the timing of significant events during the Permian–Triassic transition with high precision. These events include major stepped extinctions, beginning at ∼135 kyr and ending at ∼110 kyr below the Permian–Triassic boundary, with a duration of ∼25 kyr, followed by deposition of Lung Cam ash Bed + 13, which is equivalent to Siberian Traps volcanism is graphically correlated to a precession Time-series model, placing onset of this major volcanic event at 242 kyr before the PTB. The Meishan Beds 25 and 26, at ∼100 kyr before the Permian–Triassic boundary. In addition, the elemental geochemical, carbon and oxygen isotope stratigraphy, and magnetostratigraphy susceptibility datasets from Lung Cam allow good correlation to other Permian–Triassic boundary succession. These datasets are helpful when the conodont biostratigraphy is poorly known in sections with problems such as lithofacies variability, or is undefined, owing possibly to lithofacies exclusions, anoxia or for other reasons. The Lung Pu Permian–Triassic boundary section, ∼45 km from Lung Cam, is used to test these problems.